Predation on Rhamphocelus carbo (Pallas, 1764) (Aves: Thraupidae) by the neotropical carnivorous bat Vampyrum spectrum (Linnaeus, 1758) (Mammalia: Phyllostomidae) in a forest management area of eastern Amazon, Brazil - Hernández-Ruz, Emil José; Gonçalves, William; do Nascimento Pereira, Fabrício Otávio; França, Isadora Fernandes de; de Souza Junior, Guilherme Bueno; Santos, Caroline Guilherme; Farias, Solange (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
We report an episode of predation on the passerine bird Rhamphocelus carbo by the bat Vampyrum spectrum. This event occurred in LN Guerra Group camp, located in the Uberlândia Forest Management Unit, private property in an area of the Amazon rainforest, near Portel on Marajó Island, State of Pará, eastern Brazilian Amazon. At 5:00 a.m. on August 29th, 2020, a specimen of V. spectrum preyed on a specimen of R. carbo next to the visitors’ dormitory. The bat captured the bird by its head, leaving only its wings and feet after feeding. This predator behavior report is of interest as it demonstrates the feeding habits and natural history of a bat species considered by the IUCN Red List of Threatened Species as Near-Threatened. In addition, it is important because it was recorded by a person with no training in biology, whose interest in wild fauna was aroused due to our presence. We consider this influence a significant incentive for biodiversity preservation by operators.
Keywords: Natural history; Passeriform; Chiroptera; Tocantins River Basin